Population-level salt intake in the WHO European Region in 2022: a systematic review - Edwin Jit Leung Kwong; Stephen Whiting; Anne Charlotte Bunge; Yana Leven; Joao Breda; Ivo Rakovac; Francesco Paolo Cappuccio; Kremlin Wickramasinghe (Cambridge University Press, 2023)
Abstract Objective: The WHO recommends that adults consume less than 5 g of salt per day to reduce the risk of CVD. This study aims to examine the average population daily salt intake in the fifty-three Member States of the WHO European Region. Design: A systematic review was conducted to examine the most up-to-date salt intake data for adults published between 2000 and 2022. Data were obtained from peer-reviewed and grey literature, WHO surveys and studies, as well as from national and global experts. Setting: The fifty-three Member States of the WHO European Region. Participants: People aged 12 years or more. Results: We identified fifty studies published between 2010 and 2021. Most countries in the WHO European Region (n 52, 98 %) reported salt intake above WHO recommended maximum levels. In almost all countries (n 52, 98 %), men consume more salt than women, ranging between 5·39 and 18·51 g for men and 4·27 and 16·14 g for women. Generally, Western and Northern European countries have the lowest average salt intake, whilst Eastern European and Central Asian countries have the highest average. Forty-two percentage of the fifty-three countries (n 22) measured salt intake using 24 h urinary collection, considered the gold standard method. Conclusions: This study found that salt intakes in the WHO European Region are significantly above WHO recommended levels. Most Member States of the Region have conducted some form of population salt intake. However, methodologies to estimate salt intake are highly disparate and underestimations are very likely.